Perspectives of Polish adolescent immigrants on the Polish School in Reykjavík : benefits and challenges - Malwina Barbara Wejher 1988- (2019)
The issue of immigrants and opportunities for learning their heritage language abroad is intensively debated in the field of education. Scholars debate about the importance of heritage language learning, its benefits and challenges. Previous studies report that heritage language learning improves school achievement and communication within families, as well as contributing to higher self-esteem and ethnic identity and serving as a base for second language acquisition. This research study investigates Polish immigrant adolescents’ perspectives on attending the Polish School in Reykjavík. The paper addresses the issue of heritage language learning, studying benefits and challenges of attending heritage language classes from the perspective of Polish immigrant adolescents. The study is grounded in a social constructivist perspective that aims to explain how different perspectives and interpretations construct new knowledge. The study involves an ethnographical approach to qualitative research methods by conducting interviews and observations. Data was collected through semi-structured interviews and observations. Six Polish immigrant adolescents from the Polish School in Reykjavík were interviewed. 295 minutes were spent on observations in it during classes and free time. Data was systematized, analyzed and interpreted. Results indicated that although Polish immigrant adolescents encounter many challenges associated with attending the School, the benefits are much more valuable for them. For Polish immigrant adolescents, some of the benefits are associated with improving Polish skills and the importance of heritage language learning. Polish immigrant adolescents report that heritage language learning improves language skills and communication within the family as well as contributing to higher self-esteem. On the other hand, they negate its contribution to greater ethnic identity.